Mixed micellar solubilization for procion blue MxR entrapment and optimization of necessary parameters for micellar enhanced ultrafiltration. (February 2023) - Yusaf, Amnah; Usman, Muhammad; Ibrahim, Muhammad; Mansha, Asim; Haq, Atta ul; Rehman, Hafiza Fatima; Ali, Majid
Abstract: In this study, micellar enhanced ultrafiltration, MEUF, being an active methodology, has been employed to remove Procion Blue MxR (PBM) from synthetic effluent. MEUF is being applied to reduce the toxicity level of aqueous system using the micellar media of cationic surfactants i.e . Cetyl trimethylammonium bromide (CTAB) and cetylpyridinium chloride (CPC). Subsequently, the effect of addition of nonionic surfactant, Triton X-100 (TX-100), on solubilizing power of cationic surfactants is investigated. The values of partition coefficient and free energy of partition reflect the extent of interaction of the dye with the surfactants. Initially molecules of pollutants i.e. dye form ion pairs with ionic surfactants and, later on, the same is incorporated within micelle. Maximum value of free energy of partition ΔGp has been found to be −55.49 kJmol -1 and -50.43 kJmol in the presence of CPC and CTAB, respectively. The size of pollutant, thus, increases and, consequently, can be easily filtered. The effect of various factors i.e. concentration of surfactant, concentration of electrolyte (NaCl), transmembrane pressure, revolutions per minute (RPM) and pH, have been investigated to find the optimum conditions for maximum removal of PBM from aqueous system. The efficiency of MEUF has been assessed by calculating the values of rejection percentage and permeate flux. Both the surfactants were observed as strong candidates for PBM encapsulation but overall, maximum rejection percentage (R%) of 96.90% was attained by CPC. Graphical abstract: Image 1 Highlights: Solubilization of procion Blue MxR has been done in the micellar system. Both the cationic surfactants are the best candidates for PBM solubilization. Extent of partitioning, rejection % and permeate flux has been studied. Up to 95% rejection efficiency has been observed.